The Routledge companion to media and gender - Carter, Cynthia, 1959-; Steiner, Linda; McLaughlin, Lisa (London : Routledge, 2014)
'The Routledge Companion to Media and Gender offers a comprehensive examination of media and gender studies, charting its histories, investigating ongoing controversies, and assessing future trends.The 59 chapters in this volume, written by leading researchers from around the world, provide scholars and students with an engaging and authoritative survey of current thinking in media and gender research.The Companion includes the following features: With each chapter addressing a distinct, concrete set of issues, the volume includes research from around the world to engage readers in a broad array of global and transnational issues and intersectional perspectives.Authors address a series of important questions that have consequences for current and future thinking in the field, including postfeminism, sexual violence, masculinity, media industries, queer identities, video games, digital policy, media activism, sexualization, docusoaps, teen drama, cosmetic surgery, media Islamophobia, sport, telenovelas, news audiences, pornography, and social and mobile media.A range of academic disciplines inform exploration of key issues around production and policymaking, representation, audience engagement, and the place of gender in media studies.The Routledge Companion to Media and Gender is an essential guide to the central ideas, concepts and debates currently shaping media and gender research'--
Includes bibliographical references and index.
Keywords: Sex role in mass media; Mass media and culture